2017
DOI: 10.3390/molecules22101626
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenic Effect of Spices Due to Phenolic and Flavonoid Compounds—In Vitro Evaluation on Prostate Cells

Abstract: This study shows the effects of spices, and their phenolic and flavonoid compounds, on prostate cell lines (PNT1A, 22RV1 and PC3). The results of an MTT assay on extracts from eight spices revealed the strongest inhibitory effects were from black pepper and caraway seed extracts. The strongest inhibitory effect on prostatic cells was observed after the application of extracts of spices in concentration of 12.5 mg·mL−1. An LC/MS analysis identified that the most abundant phenolic and flavonoid compounds in blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…These are significant findings which demonstrate that these Apiaceae species may be potentially protective against estrogenmediated breast cancer. In another study on the in vitro evaluation on prostate cells, Lackova et al (2017) showed that the extracts from black pepper and caraway seed gave the strongest inhibitory effect on prostatic cells using the Cell-Line Proliferative Activity Testing (MTT Assay). This is used to evaluate the cells' metabolic activity and provide the cytotoxicity of the tested compounds.…”
Section: Anti-inflammatory Effects Of Spices and Herbsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are significant findings which demonstrate that these Apiaceae species may be potentially protective against estrogenmediated breast cancer. In another study on the in vitro evaluation on prostate cells, Lackova et al (2017) showed that the extracts from black pepper and caraway seed gave the strongest inhibitory effect on prostatic cells using the Cell-Line Proliferative Activity Testing (MTT Assay). This is used to evaluate the cells' metabolic activity and provide the cytotoxicity of the tested compounds.…”
Section: Anti-inflammatory Effects Of Spices and Herbsmentioning
confidence: 99%
“…Westerterp -Platenga et al, 2006;Zanzer et al, 2016 Enhancing nutrient bioavailability-piperine help assist efficient permeation through the epithelial barrier in the intestine and thus enhances absorption of specific nutrients, bioactives (curcumin and tea polyphenols) and drugs functioning as bioavailability enhancer Khajuria et al, 1998;Shoba et al, 1998;Khajuria et al, 2002;Srinivasan, 2007;Rinwa & Kumar 2012Johnson et al, 2011 Naringenin chalcone in black pepper was identified as a potent inhibitor of the growth of prostate cells Lackova et al, 2017 Turmeric Curcuminoids including curcumin (diferuloylmethane), demethoxycurcumin, bisdemethoxycurcumin, tetrahydrocurcumin Antioxidative and anti-inflammatory effects-curcumin can scavenge free radicals, inhibited lipid peroxidation, LDL and DNA oxidation;…”
Section: Referencesmentioning
confidence: 99%
“…In another study on the in vitro evaluation on prostate cells, Lackova et al (2017) showed that the extracts from black pepper and caraway seed gave the strongest inhibitory effect on prostatic cells using the Cell-Line Proliferative Activity Testing (MTT Assay). This is used to evaluate the cells' metabolic activity and provide the cytotoxicity of the tested compounds.…”
Section: Anti-inflammatory Effects Of Spices and Herbsmentioning
confidence: 99%
“…The activity of the black pepper extract was postulated to be due to 3,4-dihydroxybenzaldehyde and naringenin chalcone and from caraway seeds, neochlorogenic acid and apigenin. Lackova et al (2017) identified naringenin chalcone to be the most potent growth inhibitor of prostate cell.…”
Section: Anti-inflammatory Effects Of Spices and Herbsmentioning
confidence: 99%